2011
DOI: 10.1186/1752-1947-5-587
|View full text |Cite
|
Sign up to set email alerts
|

A family presenting with multiple endocrine neoplasia type 2B: A case report

Abstract: IntroductionMultiple endocrine neoplasia 2B, a rare autosomal dominant syndrome, is characterized by early onset of medullary thyroid carcinoma, pheochromocytoma, marfanoid habitus and mucosal neuromas of the tongue, lips, inner cheeks and inner eyelids. Gangliomatosis of the gastrointestinal tract and its complications may also occur in patients with this disease.Case presentationWe present the case of a 16-year-old Persian man diagnosed as having a non-invasive form of multiple endocrine neoplasia 2B (medull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…PPGLs have been suggested that are usually associated with 3 syndromes -Von Hippel-Lindau (VHL) syndrome (Hasani-Ranjbar et al 2009), multiple endocrine neoplasia type 2 (MEN 2;Hasani-Ranjbar et al 2011), and neurofi bromatosis type 1 (NF1). Around 40% of PPGLs patients have a germ line mutation in one of the 16 famous susceptibility genes: RET, NF1, VHL, succinate dehydrogenases (SDHA,SDHB,SDHC,SDHD,and SDHAF2),TMEM127,PHD1,PHD2,HIF2A,FH,, and KIF1B (Bayley et al 2010;Majidi et al 2011;Burnichon et al 2012;Darr et al 2012;Galan and Kann 2013;Letouze et al 2013;Castro-Vega et al 2014;Dahia 2014;Welander et al 2014;Yang et al 2015). In fact, there are two separate gene clusters taking part in the tumor genesis of PPGLs according to their transcriptional profi le; kinase receptorsignaling gene cluster (associated with RET/NF1/ TMEM127/MAX/ KIF1B mutations) and a pseudohypoxic gene cluster (associated with mutations in VHL/SDHx/PHD2 genes) (Nolting and Grossman 2012).…”
Section: Genetic Mutations Clustering In Ppglsmentioning
confidence: 99%
“…PPGLs have been suggested that are usually associated with 3 syndromes -Von Hippel-Lindau (VHL) syndrome (Hasani-Ranjbar et al 2009), multiple endocrine neoplasia type 2 (MEN 2;Hasani-Ranjbar et al 2011), and neurofi bromatosis type 1 (NF1). Around 40% of PPGLs patients have a germ line mutation in one of the 16 famous susceptibility genes: RET, NF1, VHL, succinate dehydrogenases (SDHA,SDHB,SDHC,SDHD,and SDHAF2),TMEM127,PHD1,PHD2,HIF2A,FH,, and KIF1B (Bayley et al 2010;Majidi et al 2011;Burnichon et al 2012;Darr et al 2012;Galan and Kann 2013;Letouze et al 2013;Castro-Vega et al 2014;Dahia 2014;Welander et al 2014;Yang et al 2015). In fact, there are two separate gene clusters taking part in the tumor genesis of PPGLs according to their transcriptional profi le; kinase receptorsignaling gene cluster (associated with RET/NF1/ TMEM127/MAX/ KIF1B mutations) and a pseudohypoxic gene cluster (associated with mutations in VHL/SDHx/PHD2 genes) (Nolting and Grossman 2012).…”
Section: Genetic Mutations Clustering In Ppglsmentioning
confidence: 99%
“…Weitere okuläre Befunde, welche mit einem MEN2b-Syndrom assoziiert sein können, sind prominente Hornhautnerven, prominente limbale Blutgefäße und subkonjunktivale Neurome [4][5][6][7]. Ein Sicca-Syndrom wurde häufig beschrieben, allerdings ist dieses sicherlich ein sehr unspezifisches Kriterium.…”
Section: Humangenetische Untersuchungunclassified
“…Hereditary and sporadic point mutations in the rearranged during transfection (RET) receptor tyrosine kinase oncogene are linked to greater than 60% of MTC cases [5]. Germline mutations in RET, seen in 98% of patients with hereditary MTC [6], are associated with several clinical conditions including familial MTC (FMTC) [7][8][9][10] multiple endocrine neoplasia (MEN) type 2A [11][12][13], and MEN2B [11,12,14].…”
Section: Introductionmentioning
confidence: 99%